Fertility and its consequence on family labour supply - Jungho Kim; Arnstein Aassve (Institute for the Study of Labor (IZA), 2006)
While a large body of literature focuses on how fertility affects female labour market participation, there are relatively few studies that examine the effect of fertility on male labour market participation. Even if the burden of child care falls mainly on women, an exogenous increase in fertility is likely to change the optimal allocation of time, therefore, the labour supply decision of both female and male in a household. This paper analyses how an exogenous increase in fertility affects labour market participation of men and women in Indonesia - a country that has seen dramatic changes in the labour market over recent decades. The finding is that women reduce their working hours in response to the higher fecundity in both rural and urban areas in Indonesia. On the other hand, the higher fecundity leads to men's increasing their working hours only in rural areas. The higher degree of specialization in response to fertility in rural areas is driven mainly by the differences in the cost of childcare rather than the characteristics of occupation or household bargaining power.
Keywords: J13; J22; J24; 330; fertility; labour supply; division of labour; Indonesia